Sap flow and growth response of Norway spruce under long-term partial rainfall exclusion at low altitude - Zavadilová, Ina; Szatniewska, Justyna; Petrík, Peter; Mauer, Oldřich; Pokorný, Radek; Stojanović, Marko (Frontiers in Plant Science, 2023)
Under ongoing climate change, more frequent and severe drought periods accompanied by heat waves are expected in the future. Under these conditions, the tree's survival is conditioned by fast recovery of functions after drought release. Therefore, in the presented study, we evaluated the effect of long-term water reduction in soil on tree water use and growth dynamics of Norway spruce. The experiment was conducted in two young Norway spruce plots located on sub-optimal sites at a low altitude of 440 m a.s.l. In the first plot (PE), 25% of precipitation throughfall was excluded since 2007, and the second one represented the control treatment with ambient conditions (PC). Tree sap flow, stem radial increment, and tree water deficit were monitored in two consecutive growing seasons: 2015-2016, with contrasting hydro-climatic conditions. Trees in both treatments showed relatively isohydric behavior reflected in a strong reduction of sap flow under the exceptional drought of 2015. Nevertheless, trees from PE treatment reduced sap flow faster than PC under decreasing soil water potential, exhibiting faster stomatal response. This led to a significantly lower sap flow of PE, compared to PC in 2015. The maximal sap flow rates were also lower for PE treatment, compared to PC. Both treatments experienced minimal radial growth during the 2015 drought and subsequent recovery of radial growth under the more the humid year of 2016. However, treatments did not differ significantly in stem radial increments within respective years. Precipitation exclusion treatment, therefore, led to water loss adjustment, but did not affect growth response to intense drought and growth recovery in the year after drought.